Analisis relevansi penerapan metode demonstrasi dalam pembelajaran bahasa jawa membaca geguritan siswa sekolah dasar - Ginari Almar Atus Ghaniy; Joko Daryanto; Sandra Bayu Kurniawan (Universitas Sebelas Maret, 2024)
This research aims to know and describe the relevance of the application of demonstration methods in learning Javanese language reading Javanese poetry in fourth grade SDN 2 Winong Academic Year 2023/2024. This research uses a qualitative research approach with case study methods. The data source in this study comes from teachers and 5 students of fourth grade. Data collection techniques in this research include observation, interview and documentation studies. The data validity techniques used are triangulation, namely, triangulation techniques and source triangulation. The data was analyzed using Milles and Hubberman's interactive analysis models. The application of the demonstration method has relevance at a certain level in learning the Javanese language reading Javanese poetry. With the demonstration method, students gain learning experience through the process of actions or experience what is learned, the process of observing, and listening through certain media and the process of listening through language. The implication of this research is that the demonstration method is one of the relevant learning methods to be applied to elementary school level students, especially to be able to achieve learning goals in the realm of skills. In addition, the demonstration method is a variety of learning that is suitable for use by all learning styles.